REPOSITIONING PANCASILA DALAM PERGULATAN IDEOLOGI-IDEOLOGI GERAKAN DI INDONESIA PASCA-REFORMASI - Muhammad Aziz Hakim (IAIN Tulungagung, 2016)
After the reformation, Indonesia became a battlefield of ideologies movement. Starting from the ideological movement that emerged after a long torporor the new ideological movement imported from abroad. This condition is as the result of that the reformers forgot the master plan of the country’sarrangements when fighting to undermine the new order. The impacts are that the ideologies fighting for the dominance in structuring the Indonesian government. Yet on the other hand Indonesia has an ideology called Pancasila. How to put the Pancasila in such a struggle of ideologies movements? There are at least four options, namely Pancasila is put in limited social contract position, Pancasila as a common platform, Pancasila as the nation’s vision, and Pancasila as the ideological state. And it seems that putting Pancasila as the ideological stateis the most appropriate choice, although it must be followed by a range of pre-conditions that must be met.Keywords: Pancasila, The ideology of the movement, Liberalism, Socialism, Islamism